Imagining the African American West - Allmendinger, Blake (Race and ethnicity in the American West., 2005)
"Much of the scholarly neglect of the "Black West" can be blamed on how the American West has been imagined, constructed, and framed in scholarship to date. In his study, Blake Allmendinger provides the appropriate theoretical, cultural, and historical contexts for understanding the literature and suggests new directions for the future of black western literature."--Jacket